Environmental services associated with the reclamation of areas degraded by mining: Potential for payments for environmental services - Souza, Caroline Almeida; Gallardo, Amarilis Lucia Casteli Figueiredo; Da Silva, Érica Donaire; De Mello, Yohana Cunha; Righi, Ciro Abbud; Solera, Maria Lucia [UNESP] (FapUNIFESP (SciELO), 2016)
This paper discusses the potential of associating environmental services (ES) with techniques for reclaiming degraded areas (RDA) used in the mining sector, considering the current trends in payments for environmental services (PES) in Brazil. A literature review with content analysis generated results which identified the ES generated for eight cases of RDA in mining. As an example, ES related to soil enhancement were found. A more extended review of general RDA techniques confirmed the potential for associating other ES to RDA techniques used in mining, an example here is the enhancement of carbon stocks. Support for actions could come from existing PES schemes, particularly for cases where the ES identified as associated with an RDA technique are related to soil and water conservation. Concluding remarks indicate that there is a potential scenario for ES diversification in the reclamation stage of mining operations. A first step towards accomplishing this diversification envisages the creation of a PES scheme specific to the mining sector. Further studies are needed to develop criteria for fostering a PES scheme specifically for the reclamation phase of mining operations in Brazil.
Keywords: Environmental services; Mining; Payment for environmental services; Reclamation of degraded areas